The Bow, Encana: Design, Monitoring, And Results Of A Deep Excavation In Downtown Calgary - Matthew Janes (Deep Foundations Institute, 2008)
The new Bow office complex will become the new headquarters of EnCana Corporation, a leading Canadian oil and gas company. The shoring system, encompassing nearly two city blocks and excavated to a depth of 20.5 m, supported surrounding utilities and buildings in downtown Calgary. Past excavations in the area experienced large amounts of rock movement, the mechanics of which were poorly understood. The focus of this paper is the design process and construction results concerning rock movement and the effectiveness of the shoring structure. A lack of information regarding the local in-situ stresses and shear band propagation in the bedrock led to research of case studies in the Calgary area and a peer review from local experts. Several geotechnical scenarios were analyzed using FLAC to account for varying residual rock stresses and the location and composition of weak rock layers suspected of causing shear band movement. Movement characteristics were predicted that would identify the rock deformation mechanic throughout the construction process. A detailed monitoring programme composed of precision monitoring targets, inclinometers, and extensometers was established to provide accuracy and redundancy in establishing the movement of the rock and excavation support structure. The results of the programme were used to identify the rock deformation mechanics and further refine the FLAC analysis. To date, monitoring indicates that localized shear band effect is the leading cause of rock movement. The phenomenon appears to be directionally dependent and strongly correlated to excavation extent.